A Validation Study of the Work Need Satisfaction Scale for Korean Working Adults - Kim, Ji-Hye; Yoo, Kieun; Lee, Seran; Lee, Ki-Hak (Frontiers in Psychology, 2021)
This study aimed to verify the reliability and validity of the Korean version of the Work Need Satisfaction Scale for working adults, based on the psychology of working theory. A total of 589 working adults in Korea responded to the online survey. Of these respondents, 339 were used for exploratory factor analysis and 250 for confirmatory factor analysis. In Stage 1, we translated all items into Korean, back-translated them into English, and then verified the accuracy of the translation. Exploratory factor analysis revealed the 5-factor structure of the Korean version of the Work Need Satisfaction Scale reflecting those of the original scale (survival needs, social contribution needs, autonomy, relatedness, and competence). The scale showed good internal consistency. In Stage 2, confirmatory factor analysis was conducted, and the results indicated that there were no significant differences between a correlational model, a higher-order model, and a higher-order self-determination needs model. Thus, we offered a higher-order self-determination needs model, which had better model fit and was consistent with the original scale and the psychology of working theoretical framework. In addition, convergent and discriminant validity were supported by correlation estimates of the Korean version of the Work Need Satisfaction Scale, and the concurrent validity showed that the Korean version of the Work Need Satisfaction Scale had a significant proportion of explained variance for outcomes. The findings support the conclusion that this study established strong internal consistency and validity for the Korean version of the Work Need Satisfaction Scale. Thus, the scale is unique and meaningful for measuring need satisfaction in work settings in Korea.